Testing methods for seed-transmitted viruses : - Albrechtsen, S. E. (CABI Publishing, 2006)
This book provides a practical guide to the commonly used detection methods for seed-transmitted viruses and viroids affecting both tropical and non-tropical crops.The first part descibes inportant aspects of seed-transmitted viral diseases. The second and main part contains principles of the detection techniques ams step by step protocols, accompanied by method optimization and comments.